The Effectiveness of Jump to Box Training on Jump Shoot Ability in Handball Games - Marsuna, Marsuna; Rusli, Muhammad; Mongsidi, Wolter; Jud, Jud; Sariul, Sariul (STKIP PGRI Jombang, 2023)
Inappropriate techniques for jumping shooting in handball games include body position, shot angle, or hand techniques which affect the accuracy and power of the shot. This research aims to determine the effectiveness of jump to box training on jump shooting ability in handball. The method used uses a quantitative method of one group pretest-posttest experimental design. The research was carried out by SMP Negeri 1 Kendari, namely 20 students who took part in extracurricular activities. The instrument used was a handball jump shoot ability test for 60 seconds using the jump to box training method. Based on hypothesis testing using the t-test, the research results obtained were 5.724 > from t table 2.093 and obtained a value of 0.000 < 0.05, it can be concluded that there is a significant influence of jum to box training to improve jump shooting ability in handball games.